Acoustic field of a pulsating cylinder in a rarefied gas: Thermoviscous and curvature effects - Ben-Ami, Y; Manela, A (American Physical Society, 2017)
We study the acoustic field of a circular cylinder immersed in a rarefied gas and subject to harmonic small-amplitude normal-to-wall displacement and heat-flux excitations. The problem is analyzed in the entire range of gas rarefaction rates and excitation frequencies, considering both single cylinder and coaxial cylinders setups. Numerical calculations are carried out via the direct simulation Monte Carlo method, applying a noniterative algorithm to impose the boundary heat-flux condition. Analytical predictions are obtained in the limits of ballistic- and continuum-flow conditions. Comparing with a reference inviscid continuum solution, the results illustrate the specific impacts of gas rarefaction and boundary curvature on the acoustic source efficiency. Inspecting the far-field properties of the generated disturbance, the continuum-limit solution exhibits an exponential decay of the signal with the distance from the source, reflecting thermoviscous effects, and accompanied by an inverse square-root decay, characteristic of the inviscid problem. Stronger attenuation is observed in the ballistic limit, where boundary curvature results in “geometric reduction” of the molecular layer affected by the source, and the signal vanishes at a distance of few acoustic wavelengths from the cylinder. The combined effects of mechanical and thermal excitations are studied to seek for optimal conditions to monitor the vibroacoustic signal. The impact of boundary curvature becomes significant in the ballistic-flow regime, where the optimal heat-flux amplitude required for sound reduction decreases with the distance from the source and is essentially a function of the acoustic-wavelength-scaled distance only.